Tracing temporal and geographic distribution of resistance to pyrethroids in the arboviral vector Aedes albopictus. - Alessandra Tancredi; Davide Papandrea; Michele Marconcini; Rebeca Carballar-Lejarazu; Mauricio Casas-Martinez; Eugenia Lo; Xiao-Guang Chen; Anna R Malacrida; Mariangela Bonizzoni (Public Library of Science (PLoS), 2020)
Background The arboviral vector Aedes albopictus became established on all continents except Antarctica in the past 50 years. A consequence of its rapid global invasion is the transmission of diseases previously confined to the tropics and subtropics occurring in temperate regions of the world, including the re-emergence of chikungunya and dengue in Europe. Application of pyrethroids is among the most widely-used interventions for vector control, especially in the presence of an arboviral outbreak. Studies are emerging that reveal phenotypic resistance and monitor mutations at the target site, the para sodium channel gene, primarily on a local scale. Methods A total of 512 Ae. albopictus mosquitoes from twelve geographic sites, including those from the native home range and invaded areas, were sampled between 2011 and 2018, and were analyzed at five codons of the para sodium channel gene with mutations predictive of resistance phenotype. Additionally, to test for the origin of unique kdr mutations in Mexico, we analyzed the genetic connectivity of southern Mexico mosquitoes with mosquitoes from home range, the Reunion Island, America and Europe. Results We detected mutations at all tested positions of the para sodium channel gene, with heterozygotes predominating and rare instance of double mutants. We observed an increase in the distribution and frequency of F1534C/L/S mutations in the ancestral China population and populations in the Mediterranean Greece, the appearance of the V1016G/I mutations as early as 2011 in Italy and mutations at position 410 and 989 in Mexico. The analyses of the distribution pattern of kdr alleles and haplotype network analyses showed evidence for multiple origins of all kdr mutations. Conclusions Here we provide the most-up-to-date survey on the geographic and temporal distribution of pyrethroid-predictive mutations in Ae. albopictus by combining kdr genotyping on current and historical samples with published data. While we confirm low levels of pyrethroid resistance in most analyzed samples, we find increasing frequencies of F1534C/S and V1016G in China and Greece or Italy, respectively. The observed patterns of kdr allele distribution support the hypothesis that on site emergence of resistance has contributed more than spread of resistance through mosquito migration/invasions to the current widespread of kdr alleles, emphasizing the importance of local surveillance programs and resistance management.